A Hierarchical Model for E-learning Implementation Challenges using AHP - Farid, Shahid; Ahmad, Rodina; Alam, Mujahid (Malaysian Journal of Computer Science, 2015)
E-learning is becoming the new paradigm of learning and training, especially in Higher Educational Institutions (HEIs) around the globe. HEIs in developing countries are struggling to shift to this new paradigm that would facilitate accommodating increasingly more learners in their own places and with their own time constraint choices. E-learning is not gaining as much attention in developing countries as anticipated in the last decade. Moreover, very little work has been done in this area of research in developing countries like Pakistan. This study contributes to formulating a hierarchical model of the challenges affecting the integration of information and communication technology in Pakistan’s HEIs. This study also contributes devised strategies and recommendations to overcome challenges by providing a roadmap for the implementation of e-learning systems in developing countries. An empirical-based research method was employed, with two surveys conducted on e-learning experts from different public universities. The factor analysis method was used to categorize challenges, while the Analytical Hierarchy Process (AHP) method was utilized to prioritize the identified challenges. The findings revealed 17 critical challenges, which were then categorized into 5 dimensions. The study’s implications in terms of research and practice, limitations and future research directions are also discussed.